Is There A Correlation Between COVID-19 and Hepatitis A and Hepatitis E Serum Antibody Level? - Alireza Abdollahi; Samaneh Salarvand; Vahid Mehrtash; Bita Jafarzadeh; Reza Ghalehtaki; Saeed Nateghi (Iranian Society of Pathology, 2022)
Background & Objective: The prevalence of COVID-19 and its severity have been observed to be on a lower level in underdeveloped countries with poorer standards of hygiene. This disparity may be attributed to the higher seroprevalence of other viral diseases which can result in the presence of antibodies protective against COVID-19. Two of the widespread diseases in such countries are infection to hepatitis A and E viruses (HAV and HEV). In the present study, we explored the relationship between the level of antibodies against these viruses and the susceptibility to COVID-19.Methods: Ninety patients were studied in two groups of controls and cases each consisting 45 individuals. The cases were patients with the clinical symptoms of COVID-19 and positive RT-PCR test results. The controls were individuals referred to the respiratory triage of Imam Khomeini Hospital Complex and were not demonstrating relevant clinical symptoms of COVID-19 and their RT-PCR test results were negative. Levels of HAV and HEV antibodies were measured and compared in these two groups.Results: The median of HAV antibody level was 13.6 (IQR=11.5-16.9) and 13.2 (IQR =10.7-14.7) in cases and controls, respectively, showing no statistically significant difference (P = 0.1). Likewise, the median of HEV antibody level was 6.7 (IQR=5.3-7.1) and 7.1 (IQR=6.3-7.5) in cases and controls, respectively, which again showed no statistically significant difference (P=0.41).Conclusion: The present study was carried out in a region with a relatively high prevalence of HAV and HEV infections. Contrary to our expectations, no statistically significant relationship was observed between the levels of antibodies against these viruses and the susceptibility to COVID-19. Further studies with larger sample sizes and in other countries are needed to come to a definite conclusion.